Human interface and the management of information. interaction, visualization, and analytics : 20th International Conference, HIMI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: interaction, visualization, and analytics : 20th International Conference, HIMI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available